Fertilizers Part 2. Sampling Section 7. Recommendations for minimum mass of increment of a solid fertilizer to be taken to be representative of the total sampling unit (BSI, 1988)
Agricultural chemicals, Agricultural materials, Fertilizers, Sampling methods, Minimum, Mass, Samples, Mathematical calculations